Pengaruh Kompetensi Kewirausahaan, Pengetahuan Manajemen, Dan Kepribadian Terhadap Kinerja Usaha Pada UMKM Cafe Sawah - Gunawan, Fany; Susyanti, Jeni; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to identify and analyze the influence of entrepreneurial competence, management knowledge and personality on the performance of Micro, Small and Medium Enterprises (UMKM). The research method used was multiple regression analysis of primary data collected through a survey from 60 UMKM respondents at Cafe Sawah. The results of the analysis show that entrepreneurial competence, management knowledge and personality have a significant positive influence on the performance of UMKM. In particular, management knowledge and personality have a greater influence on UMKM performance compared to entrepreneurial competence. These findings highlight the importance of developing entrepreneurial competencies and management knowledge in improving the performance of UMKM. Apart from that, UMKM owners also need to pay attention to personality aspects in managing their business. The implication of this research is the need for training and mentoring for UMKM owners to increase their competence and knowledge in entrepreneurship as well as the importance of personality development as effective business leaders. Keywords : Entrepreneurial Competence, Knowledge Management, Personality, MSMEs, Management